2015
DOI: 10.1063/1.4907945
|View full text |Cite
|
Sign up to set email alerts
|

Precision stacking of nanoparticle laden sessile droplets to control solute deposit morphology

Abstract: Stacking pure solvent droplets on a solid substrate is apparently impossible in the absence of an external force as the second droplet will invariably spill over the first leading to a large wetted area. However, the unique feature that emerges during the drying of a nanoparticle laden droplet is the progressively enlarging thin solid film along the evaporating sessile droplet liquid periphery. This solid interface: the edge of which we shall refer to as the agglomeration front comprises of a thin layer of nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The droplet evaporation model thus developed is first validated with new experimental results obtained from droplets observed to evaporate in an acoustic levitator. While very interesting insights can be obtained from sessile droplet evaporation, [9][10][11][12][13] after an expiratory event, the floating droplet evaporates in the absence of surface contact. Thus, the levitated droplets are similar to the droplets in atmosphere [14][15][16] compared to their sessile counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…The droplet evaporation model thus developed is first validated with new experimental results obtained from droplets observed to evaporate in an acoustic levitator. While very interesting insights can be obtained from sessile droplet evaporation, [9][10][11][12][13] after an expiratory event, the floating droplet evaporates in the absence of surface contact. Thus, the levitated droplets are similar to the droplets in atmosphere [14][15][16] compared to their sessile counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…It allows simple electronic circuits to be fabricated , outside the precincts of a clean room, design photonic crystals without sophisticated equipments. It also provides low-cost solutions to conventional medical diagnostic procedures. The sensitivity of the internal flow field and contact line dynamics of evaporating sessile droplets toward ambient conditions, solute–solvent combinations, as well as solute morphology can be exploited to custom design surface patterns . Co-axial stacking of colloidal drops allows vertical assembly in a predefined region which could be beneficial to semiconductor fabrication processes. , On the other hand, noncoalescing droplets placed closer than their respective diffusion length scales affect each other’s internal flow field via vapor-mediated interactions, leading to customizable surface morphologies . The contact line of a droplet can be reconfigured to morph the droplet curvature.…”
Section: Introductionmentioning
confidence: 99%
“…However bulk of the work has been done on single, sessile droplets and to our knowledge, no studies exist on the idea of droplet stacking except the one recently reported from our group. 25 The idea is to build a vertical stack of given material(s) of desired morphologies using evaporation induced self assembly over a predened region on a given substrate. Additive manufacturing relies on the principle of stacking powdered materials.…”
Section: Introductionmentioning
confidence: 99%
“…1; referred to as agglomeration front (A f )) has demonstrated the ability to contain liquid from subsequent droplet additions without spillage. 25 It was also demonstrated that by choosing an appropriate time delay between the deployments of two droplets, morphological features of the nal deposit pattern could be altered precisely. However, the proof of concept was limited to a single type of nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation